The quantitative analysis of the human papillomavirus DNA load in submandibular gland lesions with droplet digital polymerase chain reaction. (2nd January 2019) - Okada, Ryuhei; Ito, Taku; Nomura, Fuminori; Kirimura, Susumu; Cho, Yuichiro; Sekine, Masaki; Tateishi, Yumiko; Ariizumi, Yosuke; Asakage, Takahiro
Abstract: Background: The relationship between infection with human papillomavirus (HPV) and tumorigenesis of salivary gland remains controversial. Objectives: This study explored the relationship between HPV and salivary gland lesions as well as that of the HPV infection status and p16 INK4A immunoreactivity. The HPV DNA loads were also quantitatively evaluated. Materials and Methods: Tissue samples from 31 submandibular gland lesions were evaluated. p16 INK4A immunohistochemical (IHC) staining, nested polymerase chain reaction (PCR), DNA sequencing, and droplet digital PCR (ddPCR) were performed. Results: Non-neoplastic lesion, benign tumors, and malignant tumors were noted in 9, 16, 6 cases, respectively. p16 INK4A immunoreactivity was higher in malignant tumors than in benign tumors (50.0% vs. 6.3%). Single PCR with MY09/11 found that all samples were negative. Nevertheless, nested PCR revealed a high HPV-DNA positivity rate of 96.8%. No relationship between the HPV status and p16 INK4A immunoreactivity was shown. HPV-18 was the only subtype identified in this study. ddPCR showed significantly lower HPV-18 DNA loads in submandibular gland lesions than in oropharyngeal cancers. Conclusions: HPV-DNA positivity and p16 INK4A -immunoreactivity were not correlated in submandibular gland lesions. The loads of HPV DNA detected in this study were small. HPV positivity therefore may not be associated with tumorigenesis of the submandibular gland.